Small bowel obstruction caused by a large B-cell lymphoma in a patient with multicentric Castleman's disease: An unusual occurrence. (August 2014) - Montroni, Isacco; Sabattini, Elena; Ramadori, Eleonora; Koprivica, Vidak; Ugolini, Giampaolo; Locatelli, Francesca; Ghignone, Federico; Rosati, Giancarlo; Taffurelli, Mario; Pileri, Stefano
Multicentric Castleman's disease is a rare condition of systemic nonclonal lymph node hyperplasia. Because of its strong association with human herpes virus 8 (HHV8), the multicentric, more aggressive, form may progress to Kaposi sarcoma or non-Hodgkin lymphoma. While surgery is curative in the treatment of localized Castleman's disease, operative treatment of the diffuse form has as yet been unsatisfactory. We report the case of a patient presenting with postprandial vomiting of 1 month duration consistent with partial small bowel obstruction secondary to terminal ileum intussusception. Resection of the small bowel showed a stenosing tumor triggering the intussusception. On pathological examination, the tumor was found to be composed of HHV8-positive plasmablastic lymphoma cells. To our knowledge, this represents the first case of a complication due to the progression of multicentric Castleman's disease requiring surgical intervention for intussusception.